2022
DOI: 10.3390/molecules27134241
|View full text |Cite
|
Sign up to set email alerts
|

Amino-Functionalized Titanium Based Metal-Organic Framework for Photocatalytic Hydrogen Production

Abstract: Photocatalytic hydrogen production using stable metal-organic frameworks (MOFs), especially the titanium-based MOFs (Ti-MOFs) as photocatalysts is one of the most promising solutions to solve the energy crisis. However, due to the high reactivity and harsh synthetic conditions, only a limited number of Ti-MOFs have been reported so far. Herein, we synthesized a new amino-functionalized Ti-MOFs, named NH2-ZSTU-2 (ZSTU stands for Zhejiang Sci-Tech University), for photocatalytic hydrogen production under visible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 53 publications
(60 reference statements)
0
9
0
Order By: Relevance
“…Superior to TiO 2 , MIL-125 not only possess Ti-oxo clusters or Ti-oxo chains/sheets, but also have light harvested ligands, endowing them with promising photocatalytic activity. The adjustable structures of MIL-125, in particular, allow them to efficiently utilise solar light beyond the ultraviolet region (which accounts for only 4% of the total) 7 9 . The stability properties of MOFs mainly contain four factors, such as chemical stability, photostability, mechanical stability, and thermal stability 10 , 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Superior to TiO 2 , MIL-125 not only possess Ti-oxo clusters or Ti-oxo chains/sheets, but also have light harvested ligands, endowing them with promising photocatalytic activity. The adjustable structures of MIL-125, in particular, allow them to efficiently utilise solar light beyond the ultraviolet region (which accounts for only 4% of the total) 7 9 . The stability properties of MOFs mainly contain four factors, such as chemical stability, photostability, mechanical stability, and thermal stability 10 , 11 .…”
Section: Introductionmentioning
confidence: 99%
“…This was attributed to the mild synthesis conditions, structural features and low reactivity. 183 In all the reports, the inherent structural characteristics of a large surface area and a well-ordered porous structure have played significant role in their application as photocatalysts.…”
Section: Trends In the Application Of Metal Organic Frameworkmentioning
confidence: 99%
“…13 Ti-based MOFs (Ti-MOFs) can be used as a favorable candidate catalyst for the photocatalytic HER. 14 It is demonstrated that transition metal doping is effective for the improvement of W 2 C catalyst activity. 15 It is known that the coordination environment modulated by adjusting the oxidation state, which involves introducing oxygen atoms into the metal center, could enhance the activity of TM-doped systems.…”
Section: Introductionmentioning
confidence: 99%